(untitled) (Global Business Management Review (GBMR), 2022)
Nowadays, it is commonly accepted that external knowledge search is important for firm’s product innovation performance (PIP). However, it is still not clear, what dimensions of firms’ external knowledge search strategy are crucial in determining their product innovation success, and how firms are exploiting the external knowledge from their external knowledge search activities. This study intends to open the “black box” between different dimensions of external knowledge search strategies, and PIP by proposing absorptive capacity as the mediating variable. Employing path analysis through partial-least squares structural equation modeling (PLS-SEM) in a sample of 137 Malaysian manufacturing firms, this study found that absorptive capacity is partially mediated between collaboration depth and PIP. In this way, it provides insight that collaboration depth contributes to developing firms’ absorptive capacity, and yet, this strategy could also contribute directly to PIP. This study advances extant literature by explaining the way of a firm in attaining superior PIP from external search strategies and absorptive capacity and this provides insights for managers in developing suitable strategies to gain and sustain competitive advantages. As firms improve in its PIP, it could move up the value chain of a country, and encourage the better economic development of the nation.